Pancreatico-Pleural Fistula: A Rare Complication of Chronic Pancreatitis - Ponnappan, Arya; Vilapurathu, Jobin Kunjumon; Shaji, Anitta; Baby, Chriteena Mariyam; Shibuchan, Diya (Journal of Pharmacy Practice and Community Medicine)
Pancreatico-pleural Fistula is rare complication of chronic pancreatitis and it occurs in considerably less number of patients. We present a case of left sided pleural effusion that was attributable to pancreatico-pleural fistula. A 30-year old alcoholic patient who had worsening dyspnea, hemoptysis and intractable cough. Diagnosis is difficult due to the prevalance of respiratory symptoms than symptoms due to pancreatitis. Diagnosis is concluded by the detection of high level of amylase and lipase in pleural fluid and by ERCP. It had been managed by placing a stent on main pancreatic duct at the site of leakage by ERCP along with giving octreotide for 7 days. The patient’s symptoms was improved throughout hospitalization.
Keywords: Pancreatico-pleural fistula; Chronic pancreatitis; Pleural effusion; Amylase; Lipase.